Hubungan Penerapan Perilaku Kadarzi (Keluarga Sadar Gizi) dengan Status Gizi Balita di Kabupaten Tulungagung - Santik Wijayanti; Triska Susila Nindya (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Family conscious nutrition (Kadarzi) is an Indonesia government program that aims to address the nutrition problem. The family expected to be able to independently giving the best nutrition to improve health. Each Kadarzi indicator has an important role to resolve and prevent the occurrence of utrition problem as indicator of vitamin A supplementation is used to resolve vitamin A deficiency. Nutrition problems can be seen by using nutritional status. Children under five years are age-prone to experiencenutritional problem such as underweight, stunting, and wasting. Objective: The purpose of this study was to analyze the relationship between the application of Kadarzi behavior with the nutritional status of children under five (WAZ, HAZ, and WHZ). Method: The research was an analytic obsevation research, using cross sectional design. The sample consist of 72 toddlers in Salakkembang Village, Kalidawir Subdistrict, Tulungagung Regency. The data were collected by using weight and height measurement, also Kadarzi bahavior questionnaire. The data were analyzed using Fisher Exact test. Result: The results of the study showed that there was a correlation between Kadarzi behavior with nutitional status of toddlers based on WAZ (p=0.010), and HAZ (p=0.000) but not with WHZ (p=0.368). Conclusion: The better apllication of Kadarzi behavior, the better the nutritional status of toddlers WAZ and HAZ. Mothers should apply Kadarzi behavior to prevent toddlers from nutritional problems. ABSTRAK Latar belakang: Keluarga Sadar Gizi (Kadarzi) merupakan program pemerintah Indonesia yang bertujuan mengatasi masalah gizi. Keluarga diharapkan dapat secara mandiri mewujudkan keadaan gizi yang sebaik-baiknya untuk meningkatkan kesehatan. Setiap indikator Kadarzi memiliki peran penting untuk mengatasi dan mencegah terjadinya masalah gizi seperti indikator pemberian suplemen vitamin A digunakan untuk mengatasi kekurangan vitamin A. Masalah gizi dapat dilihat salah satunya dengan menggunakan status gizi. Balita merupakan usia yang rawan mengalami masalah gizi seperti underweight, stunting, dan wasting.Tujuan: Tujuan dari penelitian ini adalah menganalisis hubungan antara penerapan perilaku Kadarzi dengan status gizi balita (BB/U, TB/U, dan BB/TB).Metode: Penelitian ini merupakan penelitian observasinol analitik, dengan desain penelitian cross sectional. Sampel terdiri dari 72 balita di Desa Salakkembang, Kecamatan Kalidawir, Kabupaten Tulungagung. Pengumpulan data menggunakan penimbangan berat badan, tinggi badan, dan kuesioner perilaku Kadarzi. Data dianalisis menggunakan Fisher Exact test. Hasil: Hasil dari penelitian menunjukkan terhadap hubungan antara perilaku Kadarzi dengan status gizi balita BB/U (p=0,010) dan TB/U (p=0,000) namun tidak dengan BB/TB (p=0,368).Kesimpulan: Semakin baik penerapan perilaku Kadarzi maka semakin baik status gizi balita BB/U dan TB/U. Ibu dan seluruh anggota keluarga seharusnya menerapkan perilaku Kadarzi agar balita terhindar dari masalah gizi.